KEANEKARAGAMAN JENIS POHON DI KAWASAN CAGAR ALAM DUNGUS IWUL, JASINGA, BOGOR - Ruddy Polosakan; Laode Alhamd (BERITA BIOLOGI, 2017)
Dungus Iwul Nature Reserve is one of the remaining conservation areas in Java and has an unique vegetation. Study on tree biodiversity was carried out in one hectare permanent plot. The results showed that there were 78 species of 35 families and 63 genera with 1219 trees per hectare. The species of Orania sylvicola was very dominating the region, with high distribution (Frequency = 100%) and the total basal area (basal area relative; BA = 50.96%). Species of O. sylvicola (Important Value; IV = 129.48%) highly covered the area, followed by Mischocarpus sundaicus (IV = 19.93%), Diospyros frutescens (IV = 9.67%), Ficus variegata (IV = 9.38%) and Knema laurina (IV = 8.51%). Family with largest number of species was Euphorbiaceae (11 species), followed by Lauraceae (7 species) and 4 species of Fabaceae, Meliaceae and Rubiaceae.